Preconditions for the formation of the investment policy of Ukraine as a key set of measures to ensure economic development - Veselá, Natálie; Hampel, David; Yahelska, Kateryna; Krasko, Vitalii (Journal of Eastern European and Central Asian Research (JEECAR), 2022)
The article focuses on investments as a tool for solving economic development problems of the national economy. Based on the analysis of macroeconomic systems' development factors, it is concluded that it is necessary to accelerate economic development to ensure national competitiveness within the current global economy. The necessity of forming the organizational mechanism for the country's economic growth at a transitional stage of development is substantiated. The analysis of foreign investments in Ukraine is carried out. The paper defines the key points, tools, and measures for forming the corresponding mechanism on the example of Ukraine as an economic system in the transitional stage of development. The organizational scheme for economic growth by executive authorities is proposed. One of the critical roles in this mechanism is assigned to the Investment Department and Independent National Science Council; tasks and functions of these units in the structure of the agency are described.